2018
DOI: 10.1158/2159-8290.cd-17-0603
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin/ROS1 Inhibitor Synthetic Lethality in Breast Cancer

Abstract: The cell adhesion glycoprotein E-cadherin (CDH1) is commonly inactivated in breast tumors. Precision medicine approaches that exploit this characteristic are not available. Using perturbation screens in breast tumor cells with CRISPR/Cas9-engineered mutations, we identified synthetic lethality between E-cadherin deficiency and inhibition of the tyrosine kinase ROS1. Data from large-scale genetic screens in molecularly diverse breast tumor cell lines established that the E-cadherin/ROS1 synthetic lethality was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 52 publications
(72 reference statements)
1
92
0
Order By: Relevance
“…Breast cancer metastasis to gynaecological organs Kutasovic et al [45]. We also observed that ILC was more likely to colonise the uterus than IC-NST and, amongst non-GMs, ILC more frequently colonised the GI tract and less frequently the lungs and CNS compared to IC-NST.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Breast cancer metastasis to gynaecological organs Kutasovic et al [45]. We also observed that ILC was more likely to colonise the uterus than IC-NST and, amongst non-GMs, ILC more frequently colonised the GI tract and less frequently the lungs and CNS compared to IC-NST.…”
supporting
confidence: 68%
“…While ILC generally affects older women , patients in the GM cohort were relatively young (median 44 years), suggesting that young age of ILC diagnosis may be a risk factor for GM, and raising the possibility that these women could benefit from closer clinical surveillance. Moreover, ILC patients who relapsed after 5 years were significantly younger than those who relapsed within 5 years, suggesting that these women may be suitable candidates for extended endocrine therapy , addition of palbociclilb , or inclusion in emerging clinical trials specifically for E‐cadherin defective ILC . We also observed that ILC was more likely to colonise the uterus than IC‐NST and, amongst non‐GMs, ILC more frequently colonised the GI tract and less frequently the lungs and CNS compared to IC‐NST.…”
Section: Discussionmentioning
confidence: 71%
“…5 D). Further, CDH1 knockout MCF-7 cells (Bajrami et al, 2018) engulfed at the same rate as parental MCF-7 cells (Fig. 5, E–G).…”
Section: Resultsmentioning
confidence: 72%
“…ILC is the 6 th most common cancer in women, with an estimated 40,000 new cases in 2019, despite accounting for a smaller proportion of breast cancer cases (~15%) compared to IDC (~75%) 1 . ILC shows distinct signaling in pathways essential for breast cancer growth and proliferation compared to IDCsuch as the WNT4 signaling in response to estrogen stimulus or blockade 2,3 , increased PI3K/Akt signaling 4,5 , enhanced IGF1-IGF1R activation 6 , and dependency on ROS1 7 , which suggest that ILC could benefit from unique treatment strategies. The most distinguishing molecular feature of ILC is loss of E-cadherin, largely arising from inactivating CDH1 mutations.…”
Section: Introductionmentioning
confidence: 99%